Corporate Social Responsibility and Brand Image Construction: A Quantitative Analysis of the Fast-Casual Dining Industry in Indonesia - Muhammad Irsyad Baitussalam; Achmad Basofitrah; Septiana Khoirunnisak; Muhammad Samir Hadromi (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study examines the effect of Corporate Social Responsibility (CSR) on corporate image within the context of a local culinary business, focusing on Mie Gacoan Probolinggo. The research is motivated by the increasing importance of ethical business practices and growing public awareness of corporate social contributions. A quantitative approach with an explanatory design was employed to analyze the relationship between CSR and corporate image. Data were collected through structured questionnaires distributed to 100 respondents who had prior experience as customers. The sampling technique used was purposive sampling, ensuring that respondents met specific criteria relevant to the study. Data analysis was conducted using descriptive statistics, validity and reliability tests, classical assumption tests, and simple linear regression analysis. The results indicate that CSR has a positive and statistically significant effect on corporate image. The regression analysis shows that CSR contributes substantially to shaping consumer perceptions, supported by a significant t-test result and a coefficient of determination indicating a moderate explanatory power. These findings suggest that effective CSR implementation enhances public trust, strengthens reputation, and improves overall corporate image. The study also confirms that CSR serves not only as a social obligation but as a strategic tool for business sustainability, even in small and medium enterprises (SMEs). This research contributes to the literature by addressing the gap in CSR studies within the SME sector, particularly in the culinary industry, which has received limited scholarly attention compared to large corporations. It highlights the importance of contextual factors such as communication, community relevance, and organizational commitment in determining CSR effectiveness. The study offers practical implications for business practitioners, emphasizing the need to integrate CSR into core strategies and to ensure transparency and consistency in its implementation. However, this study is limited by its focus on a single case and cross-sectional design. Future research is recommended to explore broader contexts, apply longitudinal methods, and incorporate additional variables such as customer satisfaction or brand loyalty. Overall, the study reinforces the critical role of CSR in enhancing corporate image and provides a foundation for further research in similar contexts.